2022
DOI: 10.1021/acs.macromol.2c00034
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Unsaturated (Co)polyesters from Ring-Opening Copolymerization by Aluminum Bipyridine Bisphenolate Complexes with Improved Protonic Impurities Tolerance

Abstract: Synthesis of unsaturated polyesters (UPES) via ring-opening copolymerization (ROCOP) of maleic anhydride (MAH) and epoxides still remains a great challenge, because the reported catalytic systems generally showed low catalytic activity or complete deactivation at low catalyst concentration and exhibit poor tolerance to protonic impurities. In this work, we synthesized a series of bipyridine bisphenolate aluminum (BpyBph-Al) complexes and used these complexes to catalyze the MAH/ epoxide copolymerization for sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 63 publications
2
23
0
Order By: Relevance
“…S47–S53†), in agreement with prior reports for ROCOP catalyst systems containing excess chain transfer agents. 41,42 For example, Williams et al have previously reported a smooth transition from bi-modal molecular weight distribution to monomodal upon incremental addition of diol chain transfer agent equivalents (5 to 10 equiv.) to the ROCOP of cyclohexene oxide and phthalic anhydride using aluminum o -vanillin catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…S47–S53†), in agreement with prior reports for ROCOP catalyst systems containing excess chain transfer agents. 41,42 For example, Williams et al have previously reported a smooth transition from bi-modal molecular weight distribution to monomodal upon incremental addition of diol chain transfer agent equivalents (5 to 10 equiv.) to the ROCOP of cyclohexene oxide and phthalic anhydride using aluminum o -vanillin catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Ligand 13a was also reacted with copper(II) acetate to afford copper(II) complex 22f and with vanadium(V) oxychloride to afford vanadium(V) complex 22g . Between them, complexes 22a–g include examples of salen/salophen complexes for which soluble analogues are known to be four-, 31 five-, 32 and six-coordinate. 33 …”
Section: Resultsmentioning
confidence: 99%
“…This compound is well described in the literature and has found a variety of applications. 19 The lack of ready availability of similar M-alkyl reagents for Ga and In led us to search for other routes for the synthesis of [GaCl(salphen)] and [InCl(salphen)]. A salt-metathesis using K[N(SiMe 3 ) 2 ] reported by Williams and co-workers 15 for synthesis of their [InCl(salphen)] complex could be readily transferred and furnished good yields for preparation of these salphen complexes.…”
Section: Synthesis Of Group 13 Salphen Complexesmentioning
confidence: 99%